Puerto fluvial de carga sabana occidente - Alveolo pulmonar suburbano occidente calle 80 (2019)
The fluvial cargo port is born from the need to stop the heavy traffic on 13th and 80th streets, creating a port that receives all the cargo of western savannah sending it by means of water since sending cargo by this means is 130 times cheaper than by other means of transport, the fluvial port is divided into three parts water water, which includes the dock barges and container yard, ground water that includes shunting yard, and land water that includes port building.